MENINGKATKAN KEMAMPUAN KOGNITIF DENGAN METODE EKSPERIMEN PADA ANAK USIA 3 - 4 TAHUN DI PAUD AZZAITUN GENTING TANAH TAHUN PEMBELAJARAN 2018/2019 - Martina - Martina; Hanita - Hanita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2019)
This study aims to find out how the experiment method in improving student’s understanding on concept of weight for students aged 3 to 4. This study was conducted in Az-zaitun Genting Tanah Pre-school. The research subjects were twelve students of group B aged three to four, consisting of five males and seven females. The researcher applied classroom action research with two cycles, applying four stages; planning, implementation, observation and reflection. The result shows that students’ understanding on weight concept has increased. At the first cycle, students’ understanding reached 36% and increased into 79% at the second cycle. In conclusion, the experiment method is effective in improving students’ understanding on weight concept. Therefore, it is suggested that teacher to give stimulation and practice for improving students’ understanding weight concept.